2020
DOI: 10.7196/samj.2020.v110i5.13381
|View full text |Cite
|
Sign up to set email alerts
|

Hanging-related injury in Pietermaritzburg, South Africa

Abstract: Hanging is a common form of self-harm, and emergency care physicians will not infrequently be called upon to manage a survivor. [1-4] Despite the relative frequency of the injury, there is a paucity of literature on the topic and the spectrum and incidence of associated injuries are poorly described. Our current algorithm for the management of this injury is based on the resuscitation protocols of the Advanced Trauma Life Support (ATLS) Course, which essentially emphasise maintenance of an adequate airway whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
2
4
1
Order By: Relevance
“…The present study found a low rate of vascular injury in awake patients who have presented for assessment to an ED following NFS, which adds to contemporary literature suggesting 1.5-2% incidence. 6,23 Manual strangulation occurred as a subset of NFS frequently as a result of DFV which is consistent with international literature 12,24 and supports the important exploration of risk in this population. Over half of patients in the present study who underwent CT imaging had a 'ligature mark' documented on clinical examination or other signs of neck injury noted in the clinical chart.…”
Section: Discussionsupporting
confidence: 86%
“…The present study found a low rate of vascular injury in awake patients who have presented for assessment to an ED following NFS, which adds to contemporary literature suggesting 1.5-2% incidence. 6,23 Manual strangulation occurred as a subset of NFS frequently as a result of DFV which is consistent with international literature 12,24 and supports the important exploration of risk in this population. Over half of patients in the present study who underwent CT imaging had a 'ligature mark' documented on clinical examination or other signs of neck injury noted in the clinical chart.…”
Section: Discussionsupporting
confidence: 86%
“…Of patients who survived to discharge ( n = 277), 84% were functionally independent (total FIM = 12), and 10% had severe functional disabilities in feeding, expression, or locomotion (FIM <3) 10 . Similarly, from southern India, in‐hospital mortality rates of 17% were reported 11 and in‐hospital mortality rates from South Africa have been reported to be even lower at 2.5% 3 …”
Section: Discussionmentioning
confidence: 99%
“…10 Similarly, from southern India, inhospital mortality rates of 17% were reported 11 and in-hospital mortality rates from South Africa have been reported to be even lower at 2.5%. 3 In the setting of out-of-hospital cardiac arrest, however, survival has been reported to be uncommon at 1-3.3% based on studies from Australia and Europe. [12][13][14] This is supported by data from the present study with a 9% survival among patients who received pre-hospital chest compression for out-of-hospital cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations